1983
DOI: 10.1037/0012-1649.19.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Development of the conception of economic inequality: II. Explanations, justifications, and concepts of social mobility and change.

Abstract: Children and adolescents from four social classes were interviewed about their concepts of economic inequality. Adolescents were more likely than children to explain and justify inequality by referring to equity and were more fatalistic in their conceptions of change and in justifying wealth and poverty. Younger children were more likely than adolescents to claim that individual mobility and social change could be achieved through others giving money and less likely to say that social change could be achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
113
3
4

Year Published

1985
1985
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(132 citation statements)
references
References 27 publications
12
113
3
4
Order By: Relevance
“…These findings are not at odds with Berti & Bombi's (1988) or Leahy's (1981Leahy's ( , 1983 cognitive developmental theories of the construction of economic knowledge. Berti & Bombi hold that the belief in an equitable relationship between work and money emerges at 8 to 9 years of age.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…These findings are not at odds with Berti & Bombi's (1988) or Leahy's (1981Leahy's ( , 1983 cognitive developmental theories of the construction of economic knowledge. Berti & Bombi hold that the belief in an equitable relationship between work and money emerges at 8 to 9 years of age.…”
Section: Discussioncontrasting
confidence: 47%
“…Several studies of children's conceptions of social inequality have found some slight class differences, but consistent patterns are rare probably because of the different ways in which social class has been operationalized, the different questions asked and the paucity of research in this area. In general, middle-class children seem to be more conscious of social differences (Burgard et aI., 1989;Emler & Dickinson, 1985;Himmelweit, Halsey & Oppenheim, 1952;Jahoda, 1959), more likely to support inequality (Emler & Dickinson, 1985;Leahy, 1983) and more likely to attribute inequality to equity considerations such as the degree of individual effort, qualifications, intelligence and responsibility (Emler & Dickinson, 1985;Leahy, 1983).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Categories were mutually exclusive, resulting in scorable responses for most subjects. Interjudge reliability was satisfactory (see Leahy, 1981 and1983a, for more details).…”
Section: Development Of Concepts Of Economic and Social Inequality 113mentioning
confidence: 90%
“…Firstly, it has generally supported the position advocated by functionalist theory, demonstrating that as they grow older children are increasingly likely to accept that inequalities in wealth are legitimate, a trend that does not appear to be affected appreciably by children's own relative positions in the socio-economic system (e.g. Connell, 1977;Leahy, 1983). Secondly, there appears to be a developmental trend towards preference for principles of distributive justice which support an unequal distribution of wealth in society (Hook & Cook, 1979): older children favour the allocation of wealth or resources according to considerations of equity.…”
mentioning
confidence: 99%